THE IMPACTS OF COUNTRY-OF-ORIGIN, PRODUCT INVOLVEMENT, AND PRODUCT FAMILIARITY ON PRODUCT EVALUATION - Sahid Susilo Nugroho; Rokhima Rostiani; Indriyo Gitosudarmo (Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
One of the most interesting phenomena in global business is the existence of a product’s country-of-origin (COO). COO as an informational cue has been proven to affect consumer’s purchasing decisions in terms of their perception towards the product’s attributes as well as their overall evaluation of the product. The objective of this study is to investigate the impacts of country-of-origin on product evaluation in the Indonesian market by considering consumers’ product familiarity and consumers’ product involvement. Consumers’ perception of the product’s country-of-origin is assumed to have a significant influence on consumers’ considerations in evaluating the product prior to purchase. This impact is supposedly moderated by the extent that consumers are familiar with the product’s attributes and to what extent the product is important and interesting to them. A survey design was employed to test the proposed linkages among the variables.The target population of the survey was Indonesian consumers of imported products. The sample unit is the person who has experience in buying or consuming foreign products. The sample of 307 persons was drawn from Yogyakarta. This study examined televisions to represent a high involvement product. The country stimuli are Korea and Indonesia . The study applied the regression analyses and hierarchical moderated regression to test the proposed hypotheses. The study found that: (1) Indonesian consumers associate positively a product’s country-of-origin with their decision in evaluating the product for both Indonesian and Korean products, (2) Indonesian consumers consider the level of economic development of the countryof- origin in evaluating the product, in which the effect of the country-of-origin is stronger for a Korean product than an Indonesian product, (3) Indonesian consumers with different levels of product familiarity do not evaluate a product differently for both Indonesian and Korean products, (4) Indonesian consumers with different levels of product involvement evaluate a Korean product differently.